Compartmentalization of acute phase reactants Interleukin-6, C-Reactive Protein and Procalcitonin as biomarkers of intra-amniotic infection and chorioamnionitis. Issue 2 (December 2015) - Dulay, Antonette T.; Buhimschi, Irina A.; Zhao, Guomao; Bahtiyar, Mert O.; Thung, Stephen F.; Cackovic, Michael; Buhimschi, Catalin S.
Graphical abstract